The epidemiological trend of monkeypox and monkeypox-varicella zoster viruses co-infection in North-Eastern Nigeria - Stephen, Roland; Alele, Faith; Olumoh, Jamiu; Tyndall, Jennifer; Okeke, Malachy Ifeanyi; Adegboye, Oyelola (Frontiers in Public Health, 2022)
Background Monkeypox (MPX) is endemic in Nigeria, but it was first reported in Adamawa state, North-Eastern Nigeria, in January 2022. There are currently 172 cases of MPX in Nigeria, with four reported deaths, and Adamawa has the second-highest case count. Therefore, this study was undertaken to evaluate the epidemiological profile of this viral disease. Methods This is a cross-sectional study. The skin and blood samples were screened for the presence for Monkeypox virus (MPXV) and Varicella Zoster virus (VZV) DNA by real-time PCR; the clinical diagnosis was based on symptoms of visual signs of skin lesions and other clinical symptoms from January to July 2022. Results A total of 33 suspected cases aged 1–57 years [26 (79%) males vs. 7 (21%) females] were screened for MPX and VZV. Twenty-four (72.7%) were positive (6.1% were MPX only, 39% were VZV only, and 27% were both MPX and VZV). Most cases of MPX (82%), VZV (69%) and MPX-VZV co-infection (78%) occurred in males. More than half (54%) of those infected were children and adolescents between 0 and 19 years. All patients experienced body rashes and itching, and other clinical symptoms included fever, headache, mouth sores, muscle aches and lymphadenopathy. Over 64 and 86% of patients had contact with livestock and rodents, respectively. Conclusion MPXV, VZV and MPXV-VZV co-infections occurred predominantly among males and children in Adamawa state, Nigeria. Given the patient contact with rodents and livestock, further research on the animal reservoir is needed to highlight the transmission of MPXV in Adamawa.